Współczesne wyzwania dla bezpieczeństwa Polski w kontekście rosyjskich działań w regionie Europy Środkowo-Wschodniej - Jagusiak, Klaudia (Przegląd Wschodnioeuropejski, 2023)
The purpose of this article is to identify the contemporary security challenges that Poland faces in the context of activities undertaken by the Russian Federation in the region of Central and Eastern Europe. The presented conclusions are a consequence of the research carried out by the diagnostic survey method, with the use of the expert interview technique. This article was written based on research that focused on the security of the Baltic states and Poland, with particular emphasis on the aggressive policies of the Russian Federation. The findings of this research were used to inform the discussion about Poland’s security in the article. The main research problem involves identifying the security challenges that Poland faces in relation to Russian activities in Central and Eastern Europe.